BODY ACTING AND COMMUNICATING IN PHYSICAL EDUCATION: MOTOR SEMIOTICS IN VOLLEYBALL (Fiep Bulletin - online, 2014)
In attempting to address the so-called non-verbal communication as a language, researchers are engaged in a deadlock. Gesture and motor interactions of the sports games do not obey the classic linguistic mechanisms, but read the fulfillment of the principles of motor current action. We can reveal two motor-semiotic systems consisted of signs respectively very different body playful: “gestures” close to the act of the everyday life, and “praxemes” which the strong originality is to be a party to the current action. “Praxeme” generate a body  meta-communication of anticipations, feint and misinformation, who founded the subtleties wealth of sports games. Thurs as examples, several officials are presents body codes (volleyball, underwater sport, etc) very logins the double articulation of language systems. The study of body communication sports games or “motor-semiotics” requires a consideration of the internal logic of the body action which plunges in a context of fulfillment. At the heart of all competitive sport, and especially in one on one situations (tennis, etc) and team games (volleyball, etc), players from opposing teams tactically interact. Their interaction enhances decision making and movement strategy, as well as dummy moves and therefore meta-communicational practice. So, the player’s body, actively communicating, is going to be studied hereafter within the field of “motor semiotics” in volleyball, invented by Parlebas (1986 p.241).
Keywords: Motor-semiotics; body language; PE; volleyball; body acting; meta-communicational practice; internal logic